P-58 The palliative academic clinical trainees society: description and career outcomes of a novel peer support programme for academic trainees in palliative medicine. (1st March 2017) - Etkind, Simon Noah; Chin, Chloe; Lovell, Natasha; Wakefield, Dominique; Nwosu, Amara; Neoh, Karen; Schofield, Guy; Sleeman, Katherine
Abstract : Background: The UK Integrated Academic Training (IAT) pathway exists to promote the development of clinical researchers. The National Institute of Health Research (NIHR), alongside other funders, supports pre-doctoral Academic Clinical Fellow (ACF) and post-doctoral Clinical Lecturer posts for trainees across all specialties. In palliative medicine, low numbers of IATs (14 palliative medicine ACFs 2009 - 2014 compared to 114 oncology) and geographical spread mean that trainees can feel isolated. The Palliative Academic-Clinical Trainees Society (PACTs) was formed in 2012 to provide peer support and networking opportunities for this group. All palliative medicine IATs are invited to join PACTs. Annual meetings focus on peer-support/mentoring, and addressing clinical and academic training needs. Aim: To describe PACTs membership and outcomes of training for members. Methods: Evaluation of IAT career outcomes, based on an online database of PACTs membership, and comparison with national data. Results: Since inception, 23 IATs, including 17 ACFs and 6 CLs have been PACTs members. 6/9 (67%) completed ACFs have progressed to PhD posts, compared to 60% of ACFs across all specialties up to 2014. 2/9 ACFs returned to clinical training and 1/9 has a clinical consultant post. 1/3 completed CLs has gained an NIHR Clinician Scientist Fellowship, one has an honorary senior lectureship, and one has a clinical consultant post. In comparison, up to April 2014, 76% of CLs in all specialties continued in an academic post. PACTs members have also published over 100 research papers since 2009. Discussion: A national peer support network for IATs in palliative medicine is particularly important because the small number of posts limits local support. PACTs works well, and is considered helpful by members. Career progression for PACTs members compares favourably to national averages for IATs. This peer support model could be used elsewhere to support clinical academic training in palliative medicine.